Common variants in KCNN3 are associated with lone atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Glazer, Nicole L; Pfeufer, Arne; Alonso, Alvaro; Chung, Mina K; Sinner, Moritz F; de Bakker, Paul I W; Mueller, Martina; Lubitz, Steven A; Fox, Ervin; Darbar, Dawood; et al. (Nat Genet, 2010)
Atrial fibrillation (AF) is the most common sustained arrhythmia. Previous studies have identified several genetic loci associated with typical AF. We sought to identify common genetic variants underlying lone AF. This condition affects a subset of individuals without overt heart disease and with an increased heritability of AF. We report a meta-analysis of genome-wide association studies conducted using 1,335 individuals with lone AF (cases) and 12,844 unaffected individuals (referents). Cases were obtained from the German AF Network, Heart and Vascular Health Study, the Atherosclerosis Risk in Communities Study, the Cleveland Clinic and Massachusetts General Hospital. We identified an association on chromosome 1q21 to lone AF (rs13376333, adjusted odds ratio = 1.56; P = 6.3 x 10(-12)), and we replicated this association in two independent cohorts with lone AF (overall combined odds ratio = 1.52, 95% CI 1.40-1.64; P = 1.83 x 10(-21)). rs13376333 is intronic to KCNN3, which encodes a potassium channel protein involved in atrial repolarization.
Keywords: Adolescent; Adult; Aged; Atrial Fibrillation; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Introns; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Small-Conductance Calcium-Activated Potassium Channels; Young Adult

Genome-wide association study of PR interval. - Pfeufer, Arne; van Noord, Charlotte; Marciante, Kristin D; Arking, Dan E; Larson, Martin G; Smith, Albert Vernon; Tarasov, Kirill V; Müller, Martina; Sotoodehnia, Nona; Sinner, Moritz F; Verwoert, Germaine C; Li, Man; et al. (Nat Genet, 2010)
The electrocardiographic PR interval (or PQ interval) reflects atrial and atrioventricular nodal conduction, disturbances of which increase risk of atrial fibrillation. We report a meta-analysis of genome-wide association studies for PR interval from seven population-based European studies in the CHARGE Consortium: AGES, ARIC, CHS, FHS, KORA, Rotterdam Study, and SardiNIA (N = 28,517). We identified nine loci associated with PR interval at P < 5 x 10(-8). At the 3p22.2 locus, we observed two independent associations in voltage-gated sodium channel genes, SCN10A and SCN5A. Six of the loci were near cardiac developmental genes, including CAV1-CAV2, NKX2-5 (CSX1), SOX5, WNT11, MEIS1, and TBX5-TBX3, providing pathophysiologically interesting candidate genes. Five of the loci, SCN5A, SCN10A, NKX2-5, CAV1-CAV2, and SOX5, were also associated with atrial fibrillation (N = 5,741 cases, P < 0.0056). This suggests a role for common variation in ion channel and developmental genes in atrial and atrioventricular conduction as well as in susceptibility to atrial fibrillation.
Keywords: Aged; Atrial Fibrillation; Cohort Studies; Electrocardiography; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Meta-Analysis as Topic